THE ROLE OF MEDICAL-BIOLOGY FACTORS IN THE SPEECH DEVELOPMENT OF PRESCHOOL CHILDREN (Universal International Scientific Journal, 2026)
The main medical and biological factors affecting the formation and development of speech in children are considered. The role of hereditary factors, the state of development in the womb, maternal health, somatic and neurological diseases of early age are analyzed. It is emphasized that the physiological maturity of the central nervous system, hearing and articulation apparatus is of great importance for the full acquisition of speech. Attention is also paid to the issues of preventing speech development disorders
Keywords: speech; children; medical-biological factors